User experience on accessibility: person with disabilities in UiTM Perak / Muhammad Imran Sabri and Nurhidayah Samsul Rijal - Sabri, Muhammad Imran; Samsul Rijal, Nurhidayah (2023)
This research is about issues found during the travel by the PwD (Person with Disabilities) students in UiTM Seri Iskandar. The problem statement for this research is global concerns on Persons with Disabilities (PwDs), universal design and accessibility and lack of individualization. The objective for this research is to investigate the user experiences in terms of accessibility and facilities provided for PWD in UiTM Perak. The user experience is the PwD students’ experience from their college to their classroom. The research methodology used for this research are literature review, interview, journey mapping and observation. From the research methodology, some obstacles have been discovered. The findings gained from this research are advantages and disadvantages for the students from their experiences. For the recommendation for this research, the researcher found that the PwD students stated that there should be more facilities provided to make it easier for them to go to their classroom.